Tuberous xanthoma in an amputated stump - Prateek, Kumar; Chaudhary, Shyam Sundar; Kumar, Prabhat; Garg, Anu; Sachan, Sonal (Journal of Pakistan Association of Dermatologists, 2017)
Xanthomas are focal infiltrates of lipid-containing histiocytic foam cells that are usually found within the dermis or tendons. It is a clinical manifestation of lipoprotein metabolic disorders. We report a case of tuberous xanthoma in a 45-year-old woman who presented with multiple firm papules and nodules involving multiple sites of the body including the amputated right forearm with elevated serum cholesterol, triglycerides, LDL and VLDL. Â 